Cooperating on Competition in Transatlantic Economic Relations - Damro, C. author. aut Link
X, 214 p.
Keywords: In this in-depth study, Damro explains the creation of a formal cooperative framework for preventing disputes in transatlantic competition policy. The findings suggest that, while regulators remain constrained by domestic institutions, they play an important role in explaining why the cooperative framework is largely a discretionary one.